Molecular and phenotypic characterization of the vancomycin-resistant gene in bacterial isolates acquired from catheter tips - Siddiqui, Samra; Saeed, Mohd; Faisal, Syed Mohd; Akhtar, Asma; Sarim, Khan Mohd; Khan, Mahvish; Ahmad, Israr; Ahmad, Irfan (Cellular and Molecular Biology, 2017)
Gram-positive bacteria, particularly Staphylococcus aureus is a significant pathogen, not only in the hospital setting but the community also. S. aureus is a major cause of serious hospital and community-acquired infections, particularly in the colonized individuals. The emergence of vancomycin-resistant S. aureus (VRSA) strains has led to global concerns about treatments for staphylococcal infections. Until now, few strains of VRSA have been reported worldwide. The conventional disk diffusion method for determination of vancomycin sensitivity often misclassifies intermediately susceptible isolates to fully sensitive. However, non-automated minimum inhibitory concentration (MIC) detection methods are the gold standards. Hence there is a dire need of some advanced methods for rapid detection of VRSA strains. In the present study, Gram-positive clinical isolates were collected from different wards of K.G.M.U. Hospital, among them, 12 bacterial isolates were identified as Staphylococcus aureus and 18 isolates as Klebsiella spp. Genomic DNA of S. aureus was isolated and used as template in PCR for detection of the presence of van A and van X gene based on a given protocol. Nosocomial infections have an impact on morbidity and probably on mortality as well, and pose a significant economic burden. Rapid molecular identification of antibiotic-resistant strains undoubtedly helps to prevent the hospital-induced infections.